Three elderly asymptomatic SARS-CoV-2 infected patients in ICU - Feng Zhou; Ye Li; Xuan Gao; Ying Zhang (Journal of Infection in Developing Countries)
Previous studies on asymptomatic COVID-19 carriers indicated that asymptomatic infections always occurred in people in community or patients in general wards, prone to be young and middle aged people. Limited data are available for asymptomatic infections in critically ill patients in intensive care unit or elderly people. Here we reported three elderly asymptomatic SARS-CoV-2 infected patients in intensive care unit. These three elderly patients had negative CT images and 14 consecutive negative RT-PCR test results, with dynamic changes in IgG-IgM antibody levels without any clinical symptoms, which might be related to their weakened immune responses due to elder age (over 85 years old) and the history of hypertension. Therefore, combining nucleic acid RT-PCR and the IgM-IgG antibody test can provide more accurate SARS-CoV-2 infection diagnosis, especially for elderly asymptomatic patients.